Naukowo-techniczny slownik frazeologiczny angielsko-polski, polsko-angielski - Domanski, Piotr (Warszawa : Wydawnictwa Szkolne i Pedagogiczne, 1992)
An English/Polish dictionary of scientific and technical terms.
Keywords: Science -- Dictionaries; Engineering -- Dictionaries; English language -- Dictionaries -- Polish; Science -- Dictionaries -- Polish; Engineering -- Dictionaries -- Polish; Polish language -- Dictionaries -- English